Absorption edge of nanocrystalline cubic silicon carbide films - Lopin, A.V.; Semenov, A.V.; Puzikov, V.M.; Skorik, S.N. (Functional Materials, 2009)
The optical absorption edge of nanocrystalline films of cubic silicon carbide polytype (nc-SlC) obtained by direct ion deposition have been studied using optical spectroscopy. Within the 1.12-6.5 eV, three optical absorption regions have been found with different (exponential, power, and oscillating) dependences of the film absorption coefficient on the photon energy. Basing on the proposed structure model, the spectral dependence of absorption coefficient has been related to the defect states of nc-SlC, to direct and indirect optical interband transitions, and with dimensional quantization effects. Методом оптичної спектроскопії досліджено край оптичного поглинання нанокристалічних плівок кубічного політипу карбіду кремнію (nc-SiC), одержаних методом прямого іонного осадження. У діапазоні 1,12-6,5 еВ виділено три області оптичного поглинання з різною залежністю коефіцієнта поглинання плівок від енергії фотона: експоненціальною, степеневою та осциляційною. На основі запропонованої структурної моделі плівок спектральна залежність коефіцієнта поглинання пов'язується з дефектними станами nc-SiC, з оптичними прямими та непрямими міжзонними переходами та з ефектами розмірного квантування. Методом оптической спектроскопии изучен край оптического поглощения нанокристаллических плёнок кубического политипа карбида кремния (nc-SiC), полученных методом прямого ионного осаждения. В диапазоне 1,12-6,5 эВ выделены три области оптического поглощения с различной зависимостью коэффициента поглощения пленок от энергии фотона: экспоненциальной, степенной и осциллирующей. На основе предложенной структурной модели плёнок спектральная зависимость коэффициента поглощения связывается с дефектными состояниями nc-SiC, с оптическими прямыми и непрямыми межзонными переходами и эффектами размерного квантования.